2019
DOI: 10.5539/jfr.v8n3p26
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Total Polyphenolic Content and Antioxidant Potential of Mauby Bark Extracts (Colubrina arborescens) Brewed for Different Lengths of Time

Abstract: Mauby bark (Colubrina arborescens) is commonly used to make a beverage,“Mauby”, in the Caribbean and is believed to possess antiglycemic, antilipidemic, and anticarcinogenic properties. However, limited studies have been conducted to substantiate the compounds present that may confer these benefits. Therefore, the objectives of this research were to quantify the total polyphenolic content and evaluate the antioxidant capacity of Mauby bark extracts brewed in water at 30, 45, and 60 minutes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Overall, higher intakes of coffee were inversely associated with risk of colorectal cancer, suggesting potential associations between colorectal cancer risk and coffee consumption. A separate study by Embola et al (2019) assessed antioxidant activity of Mauby and found the bark to contain polyphenols which exhibited free radical scavenging activity, suggesting their potential to protect against oxidative stress within the body. As can be seen, these results are suggestive of the multitude of diseases in which plant extracts may offer protection from.…”
Section: Theoretical and Practical Implications Of The Studymentioning
confidence: 99%
“…Overall, higher intakes of coffee were inversely associated with risk of colorectal cancer, suggesting potential associations between colorectal cancer risk and coffee consumption. A separate study by Embola et al (2019) assessed antioxidant activity of Mauby and found the bark to contain polyphenols which exhibited free radical scavenging activity, suggesting their potential to protect against oxidative stress within the body. As can be seen, these results are suggestive of the multitude of diseases in which plant extracts may offer protection from.…”
Section: Theoretical and Practical Implications Of The Studymentioning
confidence: 99%
“…Flavonoid is the largest class of polyphenolic compounds that are well distributed in plants [9,22]. This class of polyphenolics is made up of about six sub-classes including; anthocyanidins, flavonols, flavanones, flavones, flavonols, and isoflavones [5,23,24]. Fig.…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
“…Polyphenolic compounds such as phenolics and flavonoids are secondary metabolites and a group of phytochemicals that are synthesized by plants to provide immunity for them against adversity [5]. Also, these classes of compounds have been demonstrated to possess excellent antioxidant activity that helps to scavenge or neutralize reactive oxygen and nitrogen (RON) species or free radicals that are known to cause oxidative stress in humans [6][7][8][9][10]1].…”
Section: Introductionmentioning
confidence: 99%